Empowering and reinforcing the identity of children with ADHD through the use of visual aids and behavioral intervention techniques - Halili, Margaret Dyan R.; San Valentin, Marc (Quezon City College of Fine Arts, University of the Philippines Diliman, 2019)
All children are born with the natural sense of curiosity and exploration. At a very young age they learn to see and experience their environment through their five senses, and its these experiences that, in their early to middle childhood, shape their identities and way of thinking.

Attention-Deficit Hyperactivity Disorder (ADHD) is a chronic neurobiological condition. People diagnosed with ADHD are impacted differently but the main areas is the attention span and memory retention, and the ability to physically control certain impulses or actions. It can be properly diagnosed as early as six and even into adulthood, but the condition is most commonly diagnosed among children.

Because the research surrounding ADHD is only relatively recent, it is not entirely understood or properly treated amongst parents, elders or even teachers. A lot of the preconceived notions and the ideas made around the label -- such as equating it to lazy or delinquent behavior, or that it doesn't even exist at all -- can be damaging to the child's social and academic developments.

ADHD is a lifelong condition and it afflicts many of today's youth in all aspects of their growth. This study focuses on the how self-identity is constructed through the beliefs and biases towards mental disorders, what beliefs are spread, and how the label determines social situations.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Bibliography: leaves 125-127
Keywords: Attention-deficit hyperactivity disorder; Behavioral intervention